Optimization of biochar yield using hydrothermal carbonization using response surface methodology for the adsorption of methylene blue / Aswwinyy Marimuthu - Aswwinyy, Marimuthu (2022)
The objective of this research study is to produce and optimise the biochar yield using DOE. In order to achieve the objective of this study, the treated separator sludge that had undergone submerged fermentation was added into a hydrothermal autoclave reactor to produce biochar with varying temperatures (150-220oC) and holding times (0.5-2.0 hours) and the yield was calculated and tabulated. The biochar was then used to study the reduction efficiency of methylene blue solution with the concentration of 50mg/L. Based on the study, it was found that the optimised condition for this research work was at temperature 150oC and holding time of 0.5 hours, where the yield produced was 74%. At these optimised conditions, adsorption studies with different concentration of methylene blue solution were conducted, where the reduction was above 90% and remained constant at 150mg/L, thereafter. As for the statistical analysis, the reaction temperature and the holding time shows significant reliability to the biochar yield produced as the p-values obtained was less than 0.05.